119 DECREASED SEXUAL FUNCTION AND TESTOSTERONE LEVELS IN WOMEN WITH HYPOPITUITARISM. (10th December 2015) - Garcia, M.; Zuckerbraun, E.; Tran, B.; Berman, J.; Bhasin, S.; Friedman, T. C.
Abstract : Objective: The psychological and physiological role of testosterone in women sexual function remains poorly understood. Women with hypopituitarism have severely diminished ovarian and adrenal androgen production and thus represent an excellent model to study the consequences of androgen deficiency. We hypothesized that women with hypopituitarism would exhibit altered sexual function as a result of androgen deficiency. Method: Total testosterone, objective sexual function (blood flow and somatosensory thresholds) and the subjective Female Sexual Function Index (FSFI) were measured in 15 women with documented hypopituitarism (median age 37.5±7.1, BMI 28.1±5.2) and 9 aged matched healthy volunteers (median age 26±9.2, BMI 25.6±4.2) in an IRB-approved study. Results: Total testosterone levels were markedly diminished among women with hypopituitarism (4.74±3.92 ng/dl) compared to normal volunteers (25.5±2.7 ng/dl, p≤0.0002). Although pre-stimulation of clitoral and labial blood flow were similar between the groups in this study, there was a trend toward decreased post-stimulation clitoral blood flow in patients with hypopituitarism (36±5.6 cm/sec) compared with healthy volunteers (48.5±4.9 cm/sec). Moreover, the hypopituitary patients (17.2±5.3 cm/sec, p≤0.05) showed decreased clitoral blood flow increment following stimulation compared to the healthy volunteers (29.5±5.2 cm/sec). Quantitative somatosensory testing showed statistically significant (p≤0.05) impairment in vibratory and thermal thresholds in patients with hypopituitarism compared to healthy volunteers. All areas (desire, arousal, lubrication, orgasm, satisfaction and pain) of the subjective FSFI in hypopituitary patients showed statistically significant (p≤0.0002) impairment compared to controls. Conclusion: Based on this data, we postulate that testosterone deficiency in women with hypopituitarism leads to impairment in both physiological and subjective sexual function. These data provide compelling rationale for placebo-controlled, randomized trials of testosterone replacement in women with hypopituitarism.